Coronavirus and the End of Economics-A Big question! - Singh, Dr. Navjit; Kaur, Harveen (The journal of contemporary issues in business and government, 2021)
Having markets locked, farmers truanting from fields and transit in cessation, is world economy likely to face a standstill? It can be the situation if synergistic steps are not taken to control the situation. The present study aims to unveil the repercussions of pandemics like COVID-19 on economy of developing countries like India. COVID-19 has not only imposed infrastructural demands on health care systems but also it is leading to escalation of economic costs in terms of suspended work schedules and disoriented productivity. It has been observed that regions which are having more economic integration with the world economy will be affected heavily as compared to regions which are less in integration with the outside world.